Male and female technology users’ acceptance of on-demand services - Yapp, Emily Hon Tshin; Chaaminy Balakrishna; Jasmine A.L. Yeap; Yuvaraj Ganesan (2018)
Purpose: This study explores the factors driving intention to adopt on-demand services such as Grab among male and female technology users in Malaysia. An integration of the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) and the Diffusion of Innovations Theory (DOI) was used in this study. Design/methodology/approach: Using a purposive sampling approach, data was collected from 330 Malaysian smartphone users via a self-administered questionnaire. Of this, 195 respondents were females and 135 were males. Data was analyzed using SPSS 20 and SmartPLS version 3.2.6. Findings: Social influence, facilitating conditions, hedonic motivation and perceived risk affect the intention to adopt on-demand services for female users. For male users, social influence and perceived risk affect their intention to adopt on-demand services. For both genders, immediacy and innovativeness contribute towards performance expectancy and effort expectancy respectively. For performance expectancy, personalization is important for females while compatibility is important for males. Limitation and future research: The generalizability of this study is somewhat limited given that respondents were skewed towards the younger segment. Nevertheless, the study is a stepping stone towards more comprehensive gender comparison studies using multi-group analysis. Practical implications: To foster faster adoption or usage of on-demand services, organizations should emphasize on facilitating conditions and hedonic motivation for female users and downplay perceived risk for male users. Social influence has a powerful presence on the acceptance of ondemand services for both genders. Organizations must ensure the immediacy aspect of on-demand services provided. Performance enhancement abilities of on-demand services should highlight the personalization feature of on-demand services to female users and the compatibility feature for male users. Originality/value: The inclusion of two variables, namely immediacy and personalization, in the framework reflects the state of new technologies in the 21st century. The inclusion of perceived risk lent some balance to the framework as a negative aspect is considered amidst all the other positive predictor variables of adoption.